2013
DOI: 10.1002/cmmi.1529
|View full text |Cite
|
Sign up to set email alerts
|

Optical imaging detection of microscopic mammary cancer in ErbB‐2 transgenic mice through the DA364 probe binding αvβ3 integrins

Abstract: Despite spontaneous tumor growth in genetically engineered mice being one of the most recognized tools for the in vivo evaluation of novel diagnostic and therapeutic anticancer compounds, monitoring early stage lesions in live animals is a goal that has yet to be achieved. A large number of targets for the molecular imaging of various diseases have been identified and many imaging technologies, including optical techniques are emerging. One of the most commonly exploited targets in tumor imaging is αv β3 integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…In this context, we have recently demonstrated that both ECs and cancer cells in mammary tumors arising in BALB-neuT mice express α v β 3 integrin, a receptor for several extracellular matrix proteins which harbor an arginine-glycine-aspartic acid (RGD) sequence [98]. α v β 3 integrin is widely considered to be a marker of the angiogenesis, tumor progression, and invasion of different types of cancer.…”
Section: Fighting Against Proangiogenic Oasmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, we have recently demonstrated that both ECs and cancer cells in mammary tumors arising in BALB-neuT mice express α v β 3 integrin, a receptor for several extracellular matrix proteins which harbor an arginine-glycine-aspartic acid (RGD) sequence [98]. α v β 3 integrin is widely considered to be a marker of the angiogenesis, tumor progression, and invasion of different types of cancer.…”
Section: Fighting Against Proangiogenic Oasmentioning
confidence: 99%
“…α v β 3 integrin is widely considered to be a marker of the angiogenesis, tumor progression, and invasion of different types of cancer. Since its level of expression correlates with cancer progression [99], we have developed a probe for the optical imaging detection of α v β 3 integrin and have shown that it can successfully detect microscopic in situ carcinomas in BALB-neuT mice, therefore proving itself to be a promising tool for the early diagnosis of breast cancer [98]. …”
Section: Fighting Against Proangiogenic Oasmentioning
confidence: 99%
See 1 more Smart Citation
“…TUBO epithelial cells (an ErbB2 + cloned cell line established from a mammary carcinoma arising in a BALB-neuT female mouse [31],[32]) were cultured in DMEM supplemented with 20% FBS. To generate non-adherent spherical clusters of cells (mammospheres), TUBO cells were detached and plated in ultra-low attachment flasks (Sigma-aldrich) at 6×10 4 viable cells/ml in mammosphere medium.…”
Section: Methodsmentioning
confidence: 99%
“…Near-infrared non invasive optical imaging was also used for detection of microscopic mammary cancer in ErbB2 transgenic mice (Conti et al, 2013). DA364, a near-infrared fluorescence arginine-glycine-aspartic acid cyclin probe that binds the integrin α v β 3 and is then taken up specifically by cancer cells was utilized for imaging.…”
Section: Developing Novel Therapeutics and Imaging Techniques Usinmentioning
confidence: 99%